ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN BERKUNJUNG DI EKOWISATA MANGROVE PASARBANGGI KABUPATEN REMBANG - Saputra, Rizky Hadi; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2019)
The purpose of this study was to determine the factors that influence tourist visiting decisions in Pasarbanggi Mangrove Ecotourism Rembang Regency. This type of research uses exploratory research with data collection methods using interviews and data collection tools using questionnaires with a sample of 100 respondents of Mangrove Marketbanggi Ecotourism tourists in Rembang Regency. using the Accidental Sampling method. The analysis technique uses validity test, reliability test, and factor test with SPSS 21.0. From the results of the study indicate that the quality of service influences the decision to visit by 80.1%, the location influences the decision to visit by 70.9%, the rate influences the decision to visit by 82.8%, the attractiveness influences the decision to visit by 78.0%. This means that the better the quality of service, tariff, location and attractiveness, the higher the decision to visit the Pasarbanggi Mangrove Ecotourism Rembang Regency. Tariff variables on visiting decision variables have a greater influence than service quality, location and attractiveness variables. Based on the results of the research, the researcher suggested that Ekowsiata Mangrove Pasarbanggi management in Rembang Regency make improvements and control on service quality by paying more attention to tourists, adding employees at certain times to maximize service to tourists, and adding incomplete facilities for the convenience of consumers.